Demonstration of Three Distinct High-Molecular-Weight Complexes between Plasminogen Activator Inhibitor Type 1 and Tissue-Type Plasminogen Activator - Ito, Tae; Suzuki, Yuko; Sano, Hideto; Honkura, Naoki; Castellino, Francis J.; Urano, Tetsumei (Thrombosis and Haemostasis, 2021)
Background Details of the molecular interaction between tissue-type plasminogen activator (tPA) and plasminogen activator inhibitor type-1 (PAI-1) remain unknown.Methods and Results Three distinct forms of high-molecular-weight complexes are demonstrated. Two of the forms were detected by mass spectrometry. The high molecular mass detected by MALDI-TOF MS (matrix-assisted laser desorption ionization-time of flight mass spectrometry) was 107,029 Da, which corresponds to the sum of molecular masses of the intact tPA (65,320 Da) and the intact PAI-1 (42,416 Da). The lower molecular mass was 104,367 Da and is proposed to lack the C-terminal bait peptide of PAI-1 (calculated mass: 3,804 Da), which was detected as a 3,808 Da fragment. When the complex was analyzed by SDS-PAGE (sodium dodecyl sulfate-polyacrylamide gel electrophoresis), only a single band was observed. However, after treatment by SDS and Triton X-100, two distinct forms of the complex with different mobilities were shown by SDS-PAGE. The higher molecular weight band demonstrated specific tPA activity on fibrin autography, whereas the lower molecular weight band did not. Peptide sequence analysis of these two bands, however, unexpectedly revealed the existence of the C-terminal cleavage peptide in both bands and its amount was less in the upper band. In the upper band, the sequences corresponding to the regions at the interface between two molecules in its Michaelis intermediate were diminished. Thus, these two bands corresponded to distinct nonacyl–enzyme complexes, wherein only the upper band liberated free tPA under the conditions employed.Conclusion These data suggest that under physiological conditions a fraction of the tPA–PAI-1 population exists as nonacylated–enzyme inhibitor complex.
Keywords: tissue-type plasminogen activator (tPA); plasminogen activator inhibitor type 1 (PAI-1); SERPIN; serine protease; fibrinolysis